2019
DOI: 10.5812/ijp.88774
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Microtensile Bond Strength of Four Glass-Containing Materials with Primary Teeth Dentin

Abstract: Background: Bonding to the tooth structure and fluoride release of the restoration are substantial factors to prevent the caries progression in children. Objectives: The aim of this study was to compare micro tensile bond strength of four glass-containing materials with primary teeth dentin. Methods: In this in-vitro study, 16 extracted primary molar were prepared and disinfected with 0.2% thymol solution. The occlusal box was prepared until a thin enamel wall remained and the dentin exposed at the pulpal floo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
2
0
Order By: Relevance
“…The superior bond strength of Cention N corroborated previous findings of Feiz et al. who reported a significantly higher micro-tensile bond strength of Cention N as compared to Zirconomer [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The superior bond strength of Cention N corroborated previous findings of Feiz et al. who reported a significantly higher micro-tensile bond strength of Cention N as compared to Zirconomer [ 27 ].…”
Section: Discussionsupporting
confidence: 89%
“…Cohesive failure was mainly seen for the conventional glass ionomer, a mixed type of failure for Zirconomer, whereas adhesive failure was most common for Cention N. The latter finding is in accordance with that of Feiz et al. [ 27 ], indicating a rupture of the bond at the tooth/restoration interface [ 29 ].…”
Section: Discussionsupporting
confidence: 86%
“…The lower values recorded for ionomers corroborate with Calvo et al 26 , which showed that adhesion to dentin occurs through hydrogen bonding to collagen; combined with ionic bond to apatite inside the dentin structure, causing low tensile strength. Feiz et al 27 observed that the bioactive material GIOMER accounted for better bond strength results in deciduous teeth than Cention N. Manuja et al 28 concluded that Fuji IX GIC (glass ionomer cement) presented a lower mean value for shear strength among all tested groups. Studies showed lower GIC adhesion performance in comparison to resin composite because its self-adhesion to dental tissue derives from an ionic exchange mechanism, according to which, polyacrylate ions replace phosphate ions on the surface of hydroxyapatite 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed Cention N has the highestdentin shear bond strength, followed by Zirconomer and GC Fuji II. 32,33 Similarly, Mazumdar et al 19 reported Cention N displays a higher bond strength value when compared to composite resin. 19 Also, when etching was considered, etched specimens of Cention N or bonded Cention N demonstrated higher bond strength than non-etched samples or conventional Cention N. 19,22 Likewise, a study by François P et al 34 Cention N displayed the highest Shear bond strength (SBS)values following universal adhesive application (33.8 MPa).…”
Section: Clinical Performance and Durability Of Cention N Versus Othe...mentioning
confidence: 97%